MtDNA mutations variously impact mtDNA maintenance throughout the human embryofetal development. (3rd February 2015) - Steffann, J.; Monnot, S.; Bonnefont, J.‐P.
<x xml:space="preserve">Abstract</x> Mitochondria are the largest generator of ATP in the cell. It is therefore expected that energy‐requiring processes such as oocyte maturation, early embryonic or fetal development, would be adversely impacted in case of mitochondrial deficiency. Human mitochondrial DNA (mtDNA) mutations constitute a spontaneous model of mitochondrial failure and offer the opportunity to study the consequences of energetic defects over fertility and embryofetal development. This review provides an update on the mtDNA metabolism in the early preimplantation embryo, and compiles data showing the impact of mtDNA mutations over mtDNA segregation. Despite convincing evidences about the essential role of mitochondria in oogenesis and preimplantation development, no correlation between the presence of a mtDNA mutation and fertilization failure, impaired oocyte quality, or embryofetal development arrest was found. In some cases, mutant cells might upregulate their mitochondrial content to overcome the bioenergetic defects induced by mtDNA mutations, and might escape negative selection. Finally we discuss some of the clinical consequences of these observations.